Sport Website Interactivity Effects: An Analysis of the Relationships between Interactivity, Attitudes, and Intentions to Revisit - Young Ik Suh; Taesoo Ahn; Paul M. Pedersen (Journal of Applied Sports Management, 2014)
The purpose of this study was to examine the theoretical relationships between three dimensions of interactivity (i.e., active user control, two-way communication, and real-time information) and website effectiveness variables (i.e., attitudes toward the sport website and intentions to revisit). In addition, this study compared the proposed interactivity model with a rival model to identify the role of attitude as a mediating factor. The Structural Equation Modeling (SEM) analysis with a convenience sample of 235 participants revealed that the proposed interactivity model performed better and was more parsimonious than the rival model. The results also indicated that the variable relating to attitudes toward the sport website was a significant mediating element between the three dimensions of interactivity and intentions to revisit the sport website.
Keywords: interactivity; sport websites; attitude; intention to revisit; SEM